Three new species of Gastropoda from the Red Sea deep waters - Bonfitto, Antonio; Taviani, Marco; Sabelli, Bruno (Zootaxa, 2026)
The discovery of three gastropod species (Mollusca) in biogenic sediments dredged from mesophotic and bathyal habitats off the coasts of Yemen and Sudan marks a noteworthy contribution to the inventory of marine biodiversity in the poorly studied Red Sea deep waters. These newly described species, Marginodostomia alibardii sp. nov., Miralda coronata sp. nov. and Iphitus marisrubri sp. nov., are currently known only from empty shells. The identification of adult Iphitus specimens in the Red Sea is particularly remarkable, given that members of this genus have previously been reported only from cold-water bathyal environments, in stark contrast to the present-day warm deep-water conditions of the Red Sea.